2015
DOI: 10.1088/0031-9155/60/11/4399
|View full text |Cite
|
Sign up to set email alerts
|

Dose rate properties of NIPAM-based x-ray CT polymer gel dosimeters

Abstract: In this work we investigate radiation dose rate dependencies of N-isopropylacrylamide (NIPAM) based polymer gel dosimeters (PGDs) used in conjunction with x-ray computed tomography imaging for radiotherapy dose verification. We define four primary forms of dose rate variation: constant mean dose rate where beam on and beam off times both vary, variable mean dose rate where beam on time varies, variable mean dose rate where beam off time varies and machine dose rate (MU min(-1)). We utilize both small (20 mL) v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…Polyacrylamide-type gels had indicated less dose rate dependence, but feature toxic behavior [20]. Similarly, NIPAM gels showed negligible variation in dose response due to the dose-rate effect [63] but also exhibited a significantly reduced sensitivity in comparison to methacrylic acid based polymer gels [17]. Different methacrylic acid (MA) based gels containing THPC as an oxygen scavenger had been distinctly impacted by the dose rate [39,52,58].…”
Section: Discussionmentioning
confidence: 99%
“…Polyacrylamide-type gels had indicated less dose rate dependence, but feature toxic behavior [20]. Similarly, NIPAM gels showed negligible variation in dose response due to the dose-rate effect [63] but also exhibited a significantly reduced sensitivity in comparison to methacrylic acid based polymer gels [17]. Different methacrylic acid (MA) based gels containing THPC as an oxygen scavenger had been distinctly impacted by the dose rate [39,52,58].…”
Section: Discussionmentioning
confidence: 99%
“…True 3D chemical dosimeters, such as polymer gel detectors, might be suitable detectors for UHDR beam dosimetry due to the high spatial resolution, energy independence, and tissue equivalence. The drawback is a known dose rate dependence [35,36]. The polymer gel dosimeter has been considered as a suitable candidate [20], however, a polymer gel FLASH study has not yet been reported.…”
Section: Chemical Dosimetersmentioning
confidence: 99%
“…Radiation properties, such as temporal stability, spatial integrity and dose-rate dependence, were also determined for NIPAM polymer gel dosimeters [ 372 , 373 ]. With a temperature dependence of 0.5 % (°C) −1 , X-ray CT imaging is less sensitive to the temperature during imaging than MRI [ 78 ].…”
Section: Readout Systemsmentioning
confidence: 99%